Aagera held on the first Sunday in October - Mumbai Archive Project Team (Jio Institute, 2024)
Aagera is traditionally held on the first Sunday in October. However, this event represents a token harvest as the monsoon season is still ongoing. The main harvest of the kharif crop begins towards the end of October, coinciding with All Souls Day on November 2.